Self-Compassionate Writing Exercises Increase College Women's Body Satisfaction. (September 2018) - Stern, Natalie G.; Engeln, Renee
In three studies, we tested the effect of self-compassionate, body-compassionate, and body-functionality-focused writing exercises on college women's body satisfaction. In Study 1, two hundred fifty-one undergraduate women completed one of the four letter-writing conditions: a general self-compassionate letter, a body-compassionate letter, a letter about body functionality, or a neutral writing task. In Study 2, two hundred forty undergraduate women completed one of the two compassion-focused conditions from Study 1, or one of the two new writing tasks that instructed participants to write either about their bodies or general selves, without any specific compassion cues. In both studies, participants in the compassion conditions reported significantly greater body satisfaction and positive affect relative to the neutral writing conditions. In Study 1, participants in the body-functionality condition also reported increased body satisfaction and positive affect relative to those in the neutral writing condition. Results for negative affect were inconclusive. In Study 3, the writing exercises were modified; we used an online format with 1, 158 sorority women in the United States. Again, results indicated that both self-compassion-focused and body-functionality-focused writing led to higher body satisfaction and higher positive affect (relative to a control condition focused on writing about a recent, positive event); however, no effect on negative affect emerged. Clinicians, educators, and activists may consider using these types of compassionate or body-functionality-focused writing exercises as brief interventions for increasing body satisfaction in young women. Additional online materials for this article are available athttps://osf.io/fvgcp